Przepływ Gazu Rozrzedzonego Między Równoległymi Ściankami - M. Grudnicki (Engineering Transactions, 1973)
The paper presents a review of methods applied to solving the problems of rarefied gas flows between infinite parallel walls. The linear and stationary case is considered. The problem is described by means of the linearized Boltzmann equations and the linearized BGK model with Maxwell boundary conditions. In the procedure of the linearization, particular attention is paid to mathematical correctness of the method; it is demonstrated that the linearization of the BGK equation is mathematically incorrect. Owing to the linearity of equations, the case in which the walls are kept at the same temperature (Couette flow) and the case when the walls are immobile (heat exchange) are considered separately. All the methods described are illustrated by simple examples. Finally, results obtained by individual authors arc compared and it is. shown that none of the methods leads to a complete analytic solution of the problem.